Peran UMKM dalam Mendorong Pertumbuhan Ekonomi Berkelanjutan - Larasati Larasati; Ahmad Subagio (Journal of Community Development and Empowerment, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving sustainable economic growth, particularly at the local level. This community service activity aims to enhance the capacity of MSME owners to face economic challenges, improve business competitiveness, and encourage the implementation of sustainability principles in business activities. The methods used in this activity include socialization, training, mentoring, and evaluation for MSME actors in the target area. The materials presented cover efficient business management, product innovation, the utilization of digital technology, and an understanding of environmentally friendly and sustainable business practices. The results of the activity indicate an increase in the knowledge and skills of MSME actors in business management, digital marketing, as well as an awareness of the importance of economic, social, and environmental sustainability. Furthermore, this activity has fostered the creation of new business opportunities, increased income, and strengthened the local economy. Active community participation and collaboration between academics, business actors, and stakeholders were crucial factors in the success of this service program. Thus, strengthening the role of MSMEs through community service activities is proven to provide a tangible contribution to inclusive and sustainable economic growth. This program is expected to serve as a model for sustainable MSME empowerment that can be replicated in other regions.